Between Art and Social Science: Scenic Composition as a Methodological Device - Lynn Froggett; Mervyn Conroy; Julian Manley; Alastair Roy (Forum: Qualitative Social Research, 2014)
The scenic composition (SC) is a methodological device enabling the synthesis and articulation of researchers' own complex experiences of events witnessed during data collection. Positioned between art and social science, it makes use of literary conventions to synthesise "experience near" accounts of data for interpretation. This article explains how the SC is composed by drawing on associative thinking and illustrates its use within a specific case study. The conceptual basis of the SC is discussed with reference to the work of LORENZER, WINNICOTT and BION. This is the first study in which four compositions, each by a different researcher, have been used to provide a multi-faceted view of a complex event, a live webcast. The compositions are presented along with researchers' reflections. Common themes and significant differences relating to life situations, histories and dispositions of the researchers emerge. The differences were expressed through choice of literary genres, which are common cultural resources. We ask what was achieved through the use of SCs compared with a thematic analysis of the webcast, and find that apart from synthesising and presentational functions, they give access to a multi-sensory range of researchers' experiences, including unconscious elements which were then available for reflexive interpretation by an interpretation panel.